Weight evolution after implantation of left ventricular assist device: Do we need to interfere?. Issue 10 (October 2020) - Vandersmissen, Katrien; Jacobs, Steven; Fresiello, Libera; Gerits, Kathleen; Roppe, Marieke; Van den Bossche, Klaartje; Droogne, Walter; Meyns, Bart
Objectives: Weight change after left ventricular assist device implantation may influence outcomes and can affect transplant candidacy. We questioned if there is a systematic weight change after left ventricular assist device implantation and examined the evolution in functional capacity. Methods: A retrospective analysis of 84 patients who received a left ventricular assist device in Universitaire Ziekenhuizen Leuven between 2008 and 2016 was performed. Patients were divided into four groups based on their baseline body mass index, and we also examined weight evolution for patients presenting with new-onset heart failure versus those suffering from chronic heart failure. Body mass index was assessed at baseline, 6, 12, 18, and 24 months. To indicate the functional capacity, we analyzed the results of routine 6-Minute Walk Test performed at 6, 12, and 18 months. Results: During the first 6 months after surgery, the underweight patients evolved to normal weight and the body mass index of the obese patients reduced significantly. Afterward, all patients gained weight. The weight loss of the obese was not maintained over time. The weight of patients with normal weight and overweight evolved to overweight and obesity, respectively. No body mass index changes were demonstrated for patients presenting with new-onset heart failure, and the body mass index of patients suffering from chronic HF significantly increased. There was a significant improvement in functional capacity at 6 months, but this level remained unchanged at 12 and 18 months after surgery. Conclusion: Although the initial 6 months evolve beneficial, all patients gain weight in the second year and do not further improve their exercise capacity.